Traditional herbal medicine: is it always safer than conventional medicine? - Ismail, Azlini (Microcredential @ IIUM, 2022)
This article highlights the issue of common misconceptions about traditional herbal medicines. At the same time, the article enlightens about the potential desired therapeutic and undesired lethal effects of herbal medicines, the possibility of herbal-drug or herbal-herbal interactions upon concurrent use, the safety and quality of herbal medicinal products in the market, the pertinent role of manufacturer, and some general precautionary advice to the consumer.